The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Higher body weight-dependent neural activation during reward processing - Maike Richter; Sophia Widera; Franziska Malz; Janik Goltermann; Lavinia Steinmann; Anna Kraus; Verena Enneking; Susanne Meinert; Jonathan Repple; Ronny Redlich; Elisabeth J. Leehr; Dominik Grotegerd; et al. (Brain Imaging and Behavior, 2023)
Obesity is associated with alterations in brain structure and function, particularly in areas related to reward processing. Although brain structural investigations have demonstrated a continuous association between higher body weight and reduced gray matter in well-powered samples, functional neuroimaging studies have typically only contrasted individuals from the normal weight and obese body mass index (BMI) ranges with modest sample sizes. It remains unclear, whether the commonly found hyperresponsiveness of the reward circuit can (a) be replicated in well-powered studies and (b) be found as a function of higher body weight even below the threshold of clinical obesity. 383 adults across the weight spectrum underwent functional magnetic resonance imaging during a common card-guessing paradigm simulating monetary reward. Multiple regression was used to investigate the association of BMI and neural activation in the reward circuit. In addition, a one-way ANOVA model comparing three weight groups (normal weight, overweight, obese) was calculated. Higher BMI was associated with higher reward response in the bilateral insula. This association could no longer be found when participants with obesity were excluded from the analysis. The ANOVA revealed higher activation in obese vs. lean, but no difference between lean and overweight participants. The overactivation of reward-related brain areas in obesity is a consistent finding that can be replicated in large samples. In contrast to brain structural aberrations associated with higher body weight, the neurofunctional underpinnings of reward processing in the insula appear to be more pronounced in the higher body weight range.

TGFβ counteracts LYVE-1-mediated induction of lymphangiogenesis by small hyaluronan oligosaccharides - Jochen Bauer; Melanie Rothley; Anja Schmaus; Luca Quagliata; Markus Ehret; Moritz Biskup; Véronique Orian-Rousseau; David G. Jackson; Ronald J. Pettis; Alfred Harvey; Stefan Bräse; Wilko Thiele; et al. (Journal of Molecular Medicine, 2018)

Meloxicam medication reduces orthodontically induced dental root resorption and tooth movement velocity: a combined in vivo and in vitro study of dental-periodontal cells and tissue - Christian Kirschneck; Matthias Meier; Kathrin Bauer; Peter Proff; Jochen Fanghänel (Cell and Tissue Research, 2017)

Sugars in the microenvironment: the sticky problem of HA turnover in tumors - Anja Schmaus; Jochen Bauer; Jonathan P. Sleeman (Cancer and Metastasis Reviews, 2014)

River flow regime and snow cover of the Pamir Alay (Central Asia) in a changing climate - Pierre Chevallier; Bernard Pouyaud; Marie Mojaïsky; Mikhaïl Bolgov; Oliver Olsson; Melanie Bauer; Jochen Froebrich (Hydrological Sciences Journal, 2014)

Applicability of Adapted Reservoir Operation for Water Stress Mitigation Under Dry Year Conditions - Oliver Olsson; Malika Ikramova; Melanie Bauer; Jochen Froebrich (Water Resources Management, 2010)

Threat sensitivity as assessed by automatic amygdala response to fearful faces predicts speed of visual search for facial expression - Patricia Ohrmann; Astrid Veronika Rauch; Jochen Bauer; Harald Kugel; Volker Arolt; Walter Heindel; Thomas Suslow (Experimental Brain Research, 2007)

Water quantity and quality dynamics of the THC — Tuyamuyun Hydroengineering Complex — And implications for reservoir operation - Jochen Froebrich; Melanie Bauer; Malika Ikramova; Oliver Olsson (Environmental Science and Pollution Research, 2007)

Key Elements in a Framework for Land Use Impact Assessment Within LCA (11 pp) - Llorenç Milà i Canals; Christian Bauer; Jochen Depestele; Alain Dubreuil; Ruth Freiermuth Knuchel; Gérard Gaillard; Ottar Michelsen; Ruedi Müller-Wenk; Bernt Rydgren (The International Journal of Life Cycle Assessment, 2007)

New editorial office - Heiko C. Becker; Christian Möllers; Albrecht E. Melchinger; Eva Bauer; Jochen C. Reif (Theoretical and Applied Genetics, 2005)

Platform environments, microfacies and systems tracts of the upper Cenomanian-lower Santonian of Sinai, Egypt - Jan Bauer; Jochen Kuss; Thomas Steuber (Facies, 2002)